Green synthesis of silver nanoparticles mediated Diospyros kaki L. (Persimmon): determination of chemical composition and evaluation of their antimicrobials and anticancer activities - Keskin, Cumali; Ölçekçi, Ali; Baran, Ayşe; Baran, Mehmet Fırat; Eftekhari, Aziz; Omarova, Sabina; Khalilov, Rovshan; Aliyev, Elvin; Sufianov, Albert; Beilerli, Aferin; Gareev, Ilgiz (Frontiers in Chemistry, 2023)
The eco-friendly synthesis of metallic nanoparticles (MNPs) using biological materials is an encouraging and innovativeness approach to nanotechnology. Among other synthesizing methods, biological methods are chosen because of their high efficiency and purity in many aspects. In this work, using the aqueous extract obtained from the green leaves of the D. kaki L. (DK); silver nanoparticles were synthesized in a short time and simply with an eco-friendly approach. The properties of the synthesized silver nanoparticles (AgNPs) were characterized using various techniques and measurements. In the characterization data of AgNPs, Maximum absorbance at 453.34 nm wavelengths, the average size distribution of 27.12 nm, the surface charge of −22.4 mV, and spherical appearance were observed. LC-ESI-MS/MS analysis was used to assess the compound composition of D. kaki leaf extract. The chemical profiling of the crude extract of D. kaki leaves revealed the presence of a variety of phytochemicals, predominantly phenolics, resulting in the identification of five major high-feature compounds: two major phenolic acids (Chlorogenic acid and Cynarin), and tree flavonol glucosides (hyperoside, quercetin-3-glucoside, and quercetin-3- D-xyloside). The components with the highest concentrations were cynarin, chlorogenic acid, quercetin-3- D-xyloside, hyperoside, and quercetin-3-glucoside, respectively. Antimicrobial results were determined by a MIC assay. The biosynthesized AgNPs exhibited strong antibacterial activity against the human and food pathogen Gram (+ and −) bacteria and good antifungal activity against pathogenic yeast. It was determined that 0.03–0.050 μg/mL concentrations ranges of DK-AgNPs were growth suppressive concentrations on all pathogen microorganisms. The MTT technique was used to study the cytotoxic effects of produced AgNPs on cancer cell lines (Glioblastoma (U118), Human Colorectal Adenocarcinoma (Caco-2), Human Ovarian Sarcoma (Skov-3) cancer cell lines, and Human Dermal Fibroblast (HDF) healthy cell line). It has been observed that they have a suppressive effect on the proliferation of cancerous cell lines. After 48 h of treatment with Ag-NPs, the DK-AgNPs were found to be extremely cytotoxic to the CaCo-2 cell line, inhibiting cell viability by up to 59.49% at a concentration of 50 g mL−1. It was found that the viability was inversely related to the DK-AgNP concentration. The biosynthesized AgNPs had dose-dependent anticancer efficacy. Because of the high concentration of bioactive chemicals in Diospyros kaki, it may be employed as a biological resource in medicinal applications. DK-AgNPs were shown to be an effective antibacterial agent as well as a prospective anticancer agent. The results provide a potential approach for the biogenic production of DK-AgNPs utilizing D. kaki aqueous leaf extract.